IDENTIFICATION OF RAINFALL CLIMATOLOGICAL PATTERNS AND ITS INTER-ANNUAL VARIABILITY DUE TO ENSO EFFECTS IN WESTERN JAVA ISLAND - Mira Christin Haloho, Dea
The rainfall pattern in the western part of Java is generally classified as a monsoonal pattern, namely a pattern with one peak of rainfall in one year. On the other hand, there are research that finds a pattern of two peaks of rainfall in one year in the region. Differences in rainfall patterns can be caused by differences in the number of stations, distribution of stations, as well as the length of data used, so that it is less able to represent rainfall in detail over large areas and complex topography. Inter-annual variations in rainfall in the region are also affected by the El Niño-Southern Oscillation (ENSO) phenomenon. ENSO significantly affects the magnitude and start of the rainy season in the study area. This study was conducted to re-detail rainfall patterns in the western part of the Java region by using the local maxima method and utilizes a larger number of stations, more evenly distributed, and has longer data. The analysis was expanded by looking at the impact of the ENSO phenomenon on rainfall patterns. This identification resulted in three rainfall patterns, namely rainfall with 1,2, and 3 peaks. Stations with 1 peak are generally located in the northern region (lowland region), while stations with 2 and 3 peaks dominate in the central to southern region (highland region) of the western part of Java region. The contrasting patterns between the lowland and highland areas show that topography is one of the factors that influence rainfall in the western part of Java. Then, the La Niña phenomenon causes an increase in rainfall values in almost all regions in the period August to November and causes an increase in the number of peaks and earlier peak times compared to the climatology. On the other hand, El Niño causes rainfall to decrease in almost all areas from June to October, but El Niño tends not to change rainfall patterns in western Java.